1997
DOI: 10.1002/(sici)1099-1379(199707)18:4<323::aid-job801>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A test of job security's direct and mediated effects on withdrawal cognitions

Abstract: SummaryTwo ®eld studies were undertaken to investigate the nature of the relationships between job security, job satisfaction, organizational commitment, and withdrawal cognitions. Study 1 was conducted in an organization immediately following its acquisition by another company N 137. Study 2 was conducted in an organization that had experienced a number of layos and expected more in the future N 188. Covariance structure analysis was used to test for direct, complete mediating, and partial mediating eects. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(58 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…For instance the need for security is one of the most -294-Journal of Industrial Engineering and Management -http://dx.doi.org/10.3926/jiem.1530 basic needs, according to Alderfer's (1969), Maslow's (1968), and McGregor's (1960 theories. Davy, Kinicki and Scheck (1997) assert that, job security refers to an individual's expectations about continuity in a job situation, and extends to concern over loss of desirable job features such as promotion opportunities and working conditions. Though Herzberg's two-factor theory posits that extrinsic or hygiene factors do not motivate, but prevent dissatisfaction and pain, it can be argued that the presence of these extrinsic factors among mine workers leads to motivation and impacting on their performance according to the empirical findings that support that claim.…”
Section: H2: There Is a Significant Relationship Between Extrinsic Momentioning
confidence: 99%
“…For instance the need for security is one of the most -294-Journal of Industrial Engineering and Management -http://dx.doi.org/10.3926/jiem.1530 basic needs, according to Alderfer's (1969), Maslow's (1968), and McGregor's (1960 theories. Davy, Kinicki and Scheck (1997) assert that, job security refers to an individual's expectations about continuity in a job situation, and extends to concern over loss of desirable job features such as promotion opportunities and working conditions. Though Herzberg's two-factor theory posits that extrinsic or hygiene factors do not motivate, but prevent dissatisfaction and pain, it can be argued that the presence of these extrinsic factors among mine workers leads to motivation and impacting on their performance according to the empirical findings that support that claim.…”
Section: H2: There Is a Significant Relationship Between Extrinsic Momentioning
confidence: 99%
“…Perceptions of job insecurity, defined as concerns about continuity in a Individual Layoff History and Voluntary Turnover ! 11 job situation (Davy, Kinicki, & Scheck, 1997), and reduced loyalty should be especially prevalent among layoff victims, who, having been previously targeted for layoff, are less likely to underestimate the threat of layoff. The job insecurity research, however, does not explicitly address the key spillover assumption underlying the lay business free-agent argument-i.e., that a layoff event induces job insecurity upon the victim's reemployment.…”
Section: Trust In Post-layoff Jobsmentioning
confidence: 99%
“…For example, certain types of organizational commitment, a psychological state that connects the individual to the organization and affects the employee's subsequent actions (Allen & Meyer, 1990), have been found to be primarily negatively related to the experiencing of job insecurity. Several studies have found that affective commitment, the emotional attachment to the organization, has been negatively associated with job insecurity (Ashford, et al, 1989;Bernhard-Oettel et al, 2011;Davy et al, 1997;Hellgren et al, 1999;Rosenblatt et al, 1999). Moreover, job insecurity has also been related to the workforce's increased resistance to change (Noer, 1993;Rosenblatt & Ruvio, 1996).…”
Section: Organizational Short-term Outcomesmentioning
confidence: 99%